Neglected no longer: Phylogenomic resolution of higher-level relationships in Solifugae - Kulkarni, Siddharth S. (2023)
Advanced sequencing technologies have expedited resolution of higher-level arthropod relationships. Yet, dark branches persist, principally among groups occurring in cryptic habitats. Among chelicerates, Solifugae (‘‘camel spiders’’) is the last order lacking a higher-level phylogeny and have thus been historically characterized as ‘‘neglected [arachnid] cousins’’. Though renowned for aggression, remarkable running speed, and xeric adaptation, inferring solifuge relationships has been hindered by inaccessibility of diagnostic morphological characters, whereas molecular investigations have been limited to one of 12 recognized families. Our phylogenomic dataset via capture of ultraconserved elements sampling all extant families recovered a well-resolved phylogeny, with two distinct groups of New World taxa nested within a broader Paleotropical radiation. Divergence times using fossil calibrations inferred that Solifugae radiated by the Permian, and most families diverged prior to the Paleogene-Cretaceous extinction, likely driven by continental breakup. We establish Boreosolifugae new suborder uniting five Laurasian families, and Australosolifugae new suborder uniting seven Gondwanan families using morphological and biogeographic signal.